Implementation Of The Convention On International Trade In Endangered Species Of Wild Fauna And Flora (Cites) In Indonesia Related To Protected Wildlife Trade Cases - Nisa Lestari; Abdullah Sulaiman; Vience Ratna Multiwijaya (Pusat Publikasi Nusantara, 2025)
Indonesia is one of the countries that ratified the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES), which is the main international instrument to regulate trade in endangered animals and plants. Therefore, as a consequence of the ratification, Indonesia is obliged to adjust its legal system which is currently contained in Law Number 32 of 2024 concerning Amendments to Law Number 5 of 1990 concerning the Conservation of Biological Natural Resources and Their Ecosystems to be in line with the principles of animal protection regulated by CITES. This article analyzes the application of CITES in Indonesia in the context of protected wildlife trafficking cases, identifies enforcement constraints, and offers policy recommendations to strengthen biodiversity protection. The methods used are literature studies, regulatory analysis, and representative case studies. The results of the study show that despite the existence of an adequate legal framework, operational obstacles, inter-agency coordination, lack of forensic capacity, and socio-economic aspects still reduce the effectiveness of CITES implementation. Recommendations include strengthening law enforcement capacity, harmonizing regulations, increasing international cooperation, and public education campaigns.